An Analysis of the Influence of Auditor Professional Skepticism and Effort on Audit Judgment Performance - Muhsin Muhsin (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN - SINTA 4, 2022)
The objective of this research is to examine the influence of auditors' professional skepticism and effort on audit judgment performance at Badan Pemeriksa Keuangan Republik Indonesia (BPK RI). The sample in this study consisted of auditors from level I to VII. Data was collected using the survey method and the purposive sampling technique. The data collected in this study came from 90 respondents and was tested using the SEM analysis technique on Warp PLS 7.0 program. The findings revealed that the auditor's professional skepticism and effort had a positive and statistically significant influence on audit judgment performance (with probability p <0.05). This research corresponds to Carpenter (2007) which states that auditors who have professional skepticism when dealing with high-risk clients will always modify audit procedures in order to achieve audit judgment performance. This suggests that auditors who have professional skepticism will be more critical in conducting audit performance assessments.